Oropharyngeal tumor cells induce COX-2 expression in peripheral blood monocytes by secretion of IL-1α - DeVoti, James A.; Israr, Mohd; Lam, Fung; Papayannakos, Christopher; Frank, Douglas K.; Kamdar, Dev P.; Pereira, Lucio M.; Abramson, Allan; Steinberg, Bettie M.; Bonagura, Vincent R. (Frontiers in Immunology, 2022)
Oropharyngeal squamous cell cancer (OPC) accounts for 3% of all cancers and greater than 1.5% of all cancer deaths in the United States, with marked treatment-associated morbidity in survivors. More than 80% of OPC is caused by HPV16. Tumors induced by HPV have been linked to impaired immune functions, with most studies focused on the local tumor microenvironment. Fewer studies have characterized the effects of these tumors on systemic responses in OPC, especially innate responses that drive subsequent adaptive responses, potentially creating feed-back loops favorable to the tumor. Here we report that elevated plasma levels of PGE2 are expressed in half of patients with OPC secondary to overexpression of COX-2 by peripheral blood monocytes, and this expression is driven by IL-1α secreted by the tumors. Monocytes from patients are much more sensitive to the stimulation than monocytes from controls, suggesting the possibility of enhanced immune-modulating feed-back loops. Furthermore, control monocytes pre-exposed to PGE2 overexpress COX-2 in response to IL-1α, simulating responses made by monocytes from some OPC patients. Disrupting the PGE2/IL-1α feed-back loop can have potential impact on targeted medical therapies.